Violent juveniles' adverse childhood experiences: Differentiating victim groups. (January 2021) - Baglivio, Michael T.; Wolff, Kevin T.; Epps, Nathan
Abstract: Purpose: Heightened exposure to Adverse Childhood Experiences (ACEs) is associated with early-onset offending, gang-involvement, reoffending, and offending chronicity. However, examining whether cumulative ACE or specific ACE exposure is related to differences in who these juveniles victimize has been neglected. Given theoretical connections between ACE exposure and the individuals youth victimize, we examine whether ACEs differentiate victims based on the juveniles' relationship to their victims among 28, 579 justice-involved adolescents who have committed violent against-person felonies. Methods: A series of logistic regression models is used to assess which covariates, including cumulative ACEs and individual ACE exposures, are associated with specified victim groups. This approach allows for better targeting of violence prevention efforts, as a more nuanced understanding of the increased likelihood to victimize specific groups lends to potential differences in treatment provision, beyond simplistic findings regarding the association between ACE exposure and increases in offending. Results: Cumulative ACEs decrease violent offending against strangers, while increasing likelihood of victimizing family, authority, and having multiple victim types, while specific ACE exposures also differentiate victim groups. Household mental health problems and household incarceration histories have the most substantial effects among individual ACEs. Conclusion: ACE exposure differentiates between groups of victims and may necessitate different treatment and intervention responses. Policy implications are discussed. Highlights: We examine if ACE exposure differentiates violent juveniles' victim groups. Higher ACEs increases victimizing family, authority, and multiple groups. Higher ACEs decreases violently victimizing strangers. Specific ACEs have different effects in predicting the type of victim groups. Differences in ACE exposure may lead to difference in one's violent victims.